Critical interplay between ruthenium oxide and water for the catalytic conversion of lignin to sustainable aviation fuel - Verma, Deepak; Chun, Hee Joon; Karanwal, Neha; Choi, Jongho; Oh, Suryun; Min Kim, Seung; Ki Kim, Seok; Kim, Jaehoon (Chemical Engineering Journal, 2024)
The production of renewable drop-in fuels from lignocellulosic biomass is desirable for achieving net-zero carbon emissions in the transportation sector. However, the high irregularity of lignin and its resistance to complete ring saturation and deoxygenation hinder its conversion to sustainable aviation fuels (SAFs) such as C7–C16 isoparaffins and alkylated cycloalkanes. In this study, we achieve the direct production of SAFs from lignin-derived oil over a nonacidic Ru/C catalyst in water. Hydrogen atoms generated by H2 dissociation combine with neighboring water molecules to produce hydronium ions, which are then transferred via H-shuttling to attack the double bonds and cyclic –OH groups of adsorbed reactants and intermediates. Density functional theory calculations suggest that hydrodeoxygenation in water decreases the activation energy for the direct hydrogenolysis of cyclic –OH groups over oxygen-vacant ruthenium oxide sites. The critical interplay between oxygen-vacant ruthenium oxide and water results in the almost-complete conversion of lignin-derived monomers, dimers, and bio-oils to desirable SAF components.
Keywords: Aviation fuel; Catalytic conversion; Hydrodeoxygenation; Lignocellulosic biomass; Native oxide layer; Native oxides; OH-groups; Oxide layer; Sustainable aviation fuel; Zero carbons; Hydrodeoxygenation; Lignin; Native oxide layer; Ruthenium; Sustainable aviation fuel